Application of genome editing technologies in rats for human disease models. Issue 2 (February 2018) - Yoshimi, Kazuto; Mashimo, Tomoji
Abstract Laboratory rats and mice are representative experimental animals for models of human disease. The emergence of genome editing technologies has enabled us to produce a variety of genetically modified animals, including rats, as a means of elucidating the in vivo functions of the gene of interest and characterizing the molecular mechanisms of human disease. Several advanced techniques for knock-in methodologies in rats are currently in development, which permit researchers to introduce precise nucleotide modifications at target sites in the rat's genome. Furthermore, recent studies with knock-out rats have revealed that observed disease phenotypes are often more similar than mouse models to those of humans. In this article, we introduce the methodologies for efficient gene manipulation in rats using genome editing technologies, and describe the advances made using rats for human disease models. We also discuss the importance of gene manipulation in animal models for the better understanding of fundamental processes among different species.